1992
DOI: 10.1111/j.1365-2621.1992.tb05458.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polypropylene and Polyester Meltblown Materials used for Food Oil Absorption

Abstract: Meltblown polypropylene and polyester and paper towels were examined for food oil absorption capacity by weight difference method. Six food oils (coconut, corn, cottonseed, olive, safflower, and sunflower) were used to include a range of fatty acid compositions. Materials were examined by scanning electron microscopy to note physical characteristics that related to absorption. Polypropylene absorbed 33.4% of the oils compared to 25.1% for polyester and 24.2% for paper towels. This was noted by the large pore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The highest capacity to collect crude oil was observed when using the finest fraction of the ground rubber particles. Likewise, when using fibrous biosorbents, Johnson et al (1973), Phifer and Costello (1992), Wei et al (2003), and Husseien et al (2009a,b) observed the highest sorption capacity for oil when using the finest denier fibers. An exception to the rule, regarding the size of sorbent particles, has been observed for a highly viscous oil; in such a case coarse particles can be an advantage (Ribeiro et al 2000).…”
Section: Particle Size and Surface Areamentioning
confidence: 96%
See 2 more Smart Citations
“…The highest capacity to collect crude oil was observed when using the finest fraction of the ground rubber particles. Likewise, when using fibrous biosorbents, Johnson et al (1973), Phifer and Costello (1992), Wei et al (2003), and Husseien et al (2009a,b) observed the highest sorption capacity for oil when using the finest denier fibers. An exception to the rule, regarding the size of sorbent particles, has been observed for a highly viscous oil; in such a case coarse particles can be an advantage (Ribeiro et al 2000).…”
Section: Particle Size and Surface Areamentioning
confidence: 96%
“…Also, it needs to be recognized that cellulosic materials constitute just one of several promising classes of sorbents that have been evaluated relative to their ability to absorb spilled oil. Other substrates that have been considered include polypropylene (PP) fibers (Zahid et al 1972;Phifer and Costello 1992;Wei et al 2003), exfoliated graphite (Inagaki et al 2000a), coal (Rethmeier and Jonas 2003), wool (Radetic et al 2003;Rajaković-Ognjanović et al 2008), chitosan (Ahmad et al 2005a,b), specialty polymers with oil-compatible groups (Jin et al 2012), highly hydrophobic sponges (Reynold et al 2001;Gui et al 2010;Choi et al 2011;Moura and Lago 2011;Zhu et al 2011a), and inorganic materials such as perlite, vermiculite, and bentonite (Teas et al 2001;Ahmad et al 2005b;Curbelo et al 2006;Moura and Lago 2011).…”
Section: Biosorption As a Remediation Strategy (Review Articles)mentioning
confidence: 99%
See 1 more Smart Citation